2005
DOI: 10.1211/jpp.57.9.0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Larrea tridentata (creosote bush) on cholesterol gallstones and bile secretion in hamsters

Abstract: Larrea tridentata (Sesse and Moc. ex DC.) Coville is used for the treatment of gallstones in traditional Mexican medicine. The possible prevention or elimination of gallstones by ethanolic and aqueous extracts of the leaves and twigs of L. tridentata was tested in hamsters fed a rich carbohydrate, fat-free diet. In addition, the effects of the ethanolic extract and its main metabolite, nordihydroguaiaretic acid, on bile secretion in the perfused liver were tested. In the experiment on prevention of gallstones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The dry ethanolic extract of the leaves at a level of 0.5% of diet fed to the hamsters completely inhibited the formation of cholesterol gallstones [86]. Chaparral contains nordihydroguaiaretic acid, which makes it effective not only in treating cholesterol gallstones but also in repairing the freeradical-induced damage caused by drugs such as amphetamine and cocaine.…”
Section: Other Antioxidants Usedmentioning
confidence: 98%
See 1 more Smart Citation
“…The dry ethanolic extract of the leaves at a level of 0.5% of diet fed to the hamsters completely inhibited the formation of cholesterol gallstones [86]. Chaparral contains nordihydroguaiaretic acid, which makes it effective not only in treating cholesterol gallstones but also in repairing the freeradical-induced damage caused by drugs such as amphetamine and cocaine.…”
Section: Other Antioxidants Usedmentioning
confidence: 98%
“…It also inhibits the enzyme lipoxygenase in the inflammatory pathway [87]. However, routine use of chaparral is controversial due to its hepatotoxicity [86].…”
Section: Other Antioxidants Usedmentioning
confidence: 99%
“…Accordingly, it has been reported that NDGA inhibited cytokine-induced NF-kB activation via its anti-oxidative activity (Brennan et al 1998). Recent reviews indicated NDGA has extremely diverse and noble activities (Arteaga et al 2005b;Chen 2009). Although some activity of NDGA was obviously related with its anti-oxidative and/or lipoxygenase inhibiting activity, most other diverse biological effects of NDGA are still under investigations searching for their precise action mechanisms (Lee et al 2003;Lü et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…NDGA is a well-known lipoxygenase inhibitor and also known as an antioxidant. It also has been shown to have some anti-cancer and anti-immune activities, but the precise mechanisms and effects were not clarified yet (Arteaga et al 2005b). To elucidate the anti-inflammatory activity of NDGA, the expression levels of COX-2, iNOS, and TNF-a were measured using qRT-PCR ( Figure 1AÁC).…”
Section: Ndga Abrogates Lps-induced Activation Of Proinflammatory Genmentioning
confidence: 99%
“…In other studies with 2% NDGA fed to rats, partial nephron obstruction preceded renal cyst development, and environmental factors were also involved (Evan and Gardner 1979;Gardner et al 1986). Interestingly, some studies indicate that NDGA is protective against other types of renal disease (Yam -Canul et al 2008), and in support of the traditional uses of Larrea, it has positive effects on the prevention of the development of cholesterol gallstones in hamsters (Arteaga et al 2005b), further indicating the considerable diversity in the outlook on possible actions of NDGA in the diet. mild to moderate hepatic necrosis; treatment not usually needed; stop the use of herbal supplement humans: loss of appetite, icterus, abdominal pain, dark-colored urine, elevated hepatic enzymes in blood Clinical Signs-In humans, the signs, typical of hepatic involvement, include nausea, loss of appetite, fatigue, pruritis, icterus, abdominal pain, dark -colored urine, and an enlarged liver.…”
Section: Larrea C Avmentioning
confidence: 93%